Assimilation (idgham) in the light of Qur’anic readings - Jaloul Dwadji, Djamel (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : The linguistic sound relies on two basic elements to give it a suggestive image that enables it to manifest and become clear, which are the vowels and the vowels as a tool and a result at the same time that carry an expressive value stored in their characteristics, and any change in the level of these two elements is directly accompanied by a change in other levels. Arabs often make sounds similar to the events they express, and one of the phonetic phenomena that has received wide attention from linguists and researchers is “diphthong” due to its nature and linguistic value. However, it was not sufficiently present in the linguistic arena until after the emergence of the science of Quranic readings as a dynamic process between adjacent sounds. It cannot be realized through theoretical research, so this research paper is devoted to introducing this sound phenomenon to the laboratory using the phonetic application (praat), which will enable us to see how this process takes place and the extent to which adjacent sounds are affected, the effect obtained from them and the added semantic value